RACIAL DIFFERENCES IN CARDIOVASCULAR RISK FACTORS AND THE DEVELOPMENT OF LEFT VENTRICULAR HYPERTROPHY - Jordan S. Sill, MD, MS; Jessica G. Woo, PhD; Philip R. Khoury, PhD; Elaine M. Urbina, MD, MS (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Factors Background: Obesity-related cardiovascular (CV) risk factors are associated with increased left ventricular mass, a risk factor for adult CV disease. Whether there are race differences in this relationship is not well described. Our aim was to utilize an existing longitudinal data set of black and white females to evaluate racial differences in the impact of CV risk factors on adiposity measured by different modalities and to determine the contribution of adiposity to increased LVM. Methods: Data from the National Growth and Health Study (NGHS), a study of racial differences in the development of obesity, were analyzed including demographics, medical history, anthropometrics, dual energy X-ray absorptiometry (DEXA), MRI (for abdominal subcutaneous and visceral fat), echocardiogram and laboratory data. NGHS enrolled 871 girls at age 9 or 10, 50% black and 50% white. In these analyses, data collected at the time of the patient's first DEXA scan (at age 20-21 years) and LVM index (LVMI) collected from the patient's last echocardiogram (at ages 24-27) were analyzed. Means and standard deviations were calculated for the total population and then stratified by race. T-tests were performed to assess for significant difference between races. Results: At baseline, black subjects had significantly higher weight, BMI, waist circumference, total fat mass by DEXA, subcutaneous fat mass by MRI, blood pressure, insulin, and glucose values. White subjects were found to have higher fasting triglyceride and total cholesterol values. LVMI was significantly greater in black subjects. Conclusions: Significant racial differences in CV risk factors and LVMI were found in young adulthood. Future analyses will address the contribution of central and peripheral adiposity measured by different modalities to these differences.